Formation of amino acids from NH3/NO2, CO2 and H2O: Implications for the prebiotic origin of biomolecules. (28th September 2015) - Singh, Amrinder; Nisha; Singh, Palwinder
<x xml:space="preserve">Abstract</x> Rationale The search for the conditions which must have prevailed in the long‐distant past during the conversion of inanimate matter into animate matter is a fascinating area of research and it continues to draw the attention of the scientific community. The initiation of life on this planet must have been preceded by the development of biomolecules, amongst which amino acids have unique importance. Formation of amino acids under a certain set of conditions is shown in the present experiments. Methods Solutions of ammonium carboxylates or the mixture of two such salts were prepared in 3:6.9:0.1 (v/v/v) acetonitrile/water/formic acid at a concentration of 50 μM. The studies were performed using a quadrupole time‐of‐flight (QqTOF) mass spectrometer. The formation of different amino acids was detected with high‐resolution mass spectrometry. Results Here, we show the formation of amino acids when a solution of ammonium salts was injected into an electrospray ionization (ESI)‐QqTOF‐MS instrument. The ammonium salts were the source of NH3 and CO2 and H2O was available in the medium. It seems that the combination of NH3, CO2, and H2O leads to the formation of amino acids. Conclusions Further to the literature reports of formation of amino acids under the reduced atmosphere represented by gases such as NH3, CH4, H2 and H2O, here we demonstrate the formation of amino acids by the combination of NH3/NO2, CO2 and water vapours in the ESI source of the mass spectrometer. Copyright © 2015 John Wiley & Sons, Ltd.